Practical fixed-time stabilization for discrete-time impulsive switched port-controlled Hamiltonian systems - Xiangyu Chen; Weiwei Sun; Xinci Gao; Dehay Yu (Nonlinear Analysis)
This paper is concerned with practical fixed-time (FT) stabilization problem of discretetime impulsive switched port-controlled Hamiltonian systems (DISPCH). First, starting with discrete-time port-controlled Hamiltonian systems, a novel controller is presented to achieve practical FT stability of the obtained closed-loop system. Moreover, in order to well handle the abrupt changes at switch moments in practical switched systems, another novel controller is presented in terms of positive-order Lyapunov functions approach and range dwell time method to make discrete-time impulsive switched port-controlled Hamiltonian system practical FT stable. Ultimately, the validity of proposed methods is illustrated by simulations.